2019
DOI: 10.2337/db19-0088
|View full text |Cite|
|
Sign up to set email alerts
|

TFAM Enhances Fat Oxidation and Attenuates High-Fat Diet–Induced Insulin Resistance in Skeletal Muscle

Abstract: Diet-induced insulin resistance (IR) adversely affects human health and life span. We show that muscle-specific overexpression of human mitochondrial transcription factor A (TFAM) attenuates high-fat diet (HFD)–induced fat gain and IR in mice in conjunction with increased energy expenditure and reduced oxidative stress. These TFAM effects on muscle are shown to be exerted by molecular changes that are beyond its direct effect on mitochondrial DNA replication and transcription. TFAM augmented the muscle tricarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 56 publications
(60 reference statements)
5
69
0
Order By: Relevance
“…Muscle-specific overexpression of mtTFA attenuates the effects of high-fat diet on fat gain and insulin resistance in mice. Beyond its direct effect on mitochondrial DNA replication and transcription, mtTFA overexpression increased Krebs cycle, citrate synthase and fatty acid oxidation in concert with higher β-oxidation capacity [49]. Thus, similar effects by PLC may be hypothesized at ovarian level and investigated in further studies.…”
Section: Discussionmentioning
confidence: 91%
“…Muscle-specific overexpression of mtTFA attenuates the effects of high-fat diet on fat gain and insulin resistance in mice. Beyond its direct effect on mitochondrial DNA replication and transcription, mtTFA overexpression increased Krebs cycle, citrate synthase and fatty acid oxidation in concert with higher β-oxidation capacity [49]. Thus, similar effects by PLC may be hypothesized at ovarian level and investigated in further studies.…”
Section: Discussionmentioning
confidence: 91%
“…Gene variants in mitochondrial-function-related nuclear DNA lead to relatively mildly impaired mitochondrial function, whereas classical mtDNA gene variants typically cause a severe reduction in mitochondrial function with neurological deficits and β-cell failure. In contrast to genetic and acquired alterations that lead to mild impairments in mitochondrial activity and a predisposition to ectopic lipid accumulation and insulin resistance, alterations that lead to severe reductions in mitochondrial activity (for example, mtDNA variants) result in increased dependency on anaerobic glycolysis, hyperlactaemia and increased glucose metabolism [92][93][94] . In support of this hypothesis, a recent European GWAS reported that a nonsynonymous variant of N-acetyltransferase 2 (NAT2) is associated with insulin resistance and related traits as well as with decreased adipocyte differentiation, insulin-mediated glucose uptake and increased WAT lipolysis 95 .…”
Section: Insulin Resistance In Skeletal Musclementioning
confidence: 99%
“…One of the cardinal benefits of exercise training (Ext) is the regulation of whole-body glucose homeostasis, which is differently regulated via distinct mechanisms between before exercise and recovery from exercise. During an exercise bout, the activated muscle displays increased glucose uptake in an insulin-independent manner [8]. Furthermore, after an exercise bout, skeletal muscle insulin sensitivity and responsiveness are enhanced even at rest [9].…”
Section: Introductionmentioning
confidence: 99%